Kaji eksperimental pengaruh debit dan kemiringan poros terhadap daya mekanik prototype turbin ulir tipe AH-01 dan AH-02 - Adly Havendri; Yul Hizhar; Oding Syamiro Perdana (METAL: Jurnal Sistem Mekanik dan Termal, 2021)
The potential for renewable energy sources in Indonesia is rich enough to be used as an alternative energy source. The availability of hydro energy potential can be developed into a Mini Hydro Power Plant. One type of turbine that has been developed is the Archimedean turbine which is capable of utilizing low headwater sources. The AH-01 and AH-02 screw turbine prototypes have been made at Andalas University and testing was necessary to determine the optimal discharge for mechanical performance. Testing of the screw turbine prototype type AH-01 (screw angle 23°) and AH-02 (screw angle 26°) was carried out by varying the flow rate and shaft angle for the two types of screw turbine prototypes to determine mechanical performance and efficiency of the turbines. The test results show that the AH-02 screw turbine prototype has higher mechanical power than the AH-01 screw turbine prototype. The maximum mechanical power of each AH-01 and AH-02 screw turbine prototype is 5.77 and 7.54 Watts at a flow rate of 0.00139 m3/s.